Thermoelastic equation of state of boron suboxide B₆O up to 6 GPa and 2700 K: simplified anderson-grüneisen model and thermodynamic consistency - Kurakevych, O.O.; Solozhenko, V.L. (Сверхтвердые материалы, 2014)
The p-V-T equation of state of superhard boron suboxide B₆O has been measured up to 6 GPa and 2700 K using multianvil technique and synchrotron X-ray diffraction. To fit the experimental data, the theoretical p-V-T equation of state has been derived in approximation of the constant value of the Anderson-Grüneisen parameter δT. Bulk modulus B₀ =181 GPa and its first pressure derivative B₀' = 6 at 300 K; two parameters describing thermal expansion at 0.1 MPa, i.e., a = 1.4×10–5 K–1 and b = 5×10–9 K–2 as well as dT = 6 have been included in the model. The good agreement between fitted and experimental isobars has been achieved to the absolute volume changes up to 5 % as compared to the volume at standard conditions, V0. The fitted thermal expansion at 0.1 MPa well consistent with the experimental data as well as with ambient-pressure heat capacity cp, bulk modulus B₀ and dT describing its evolution with volume and temperature have been discussed. The fitted value of Grüneisen parameter g = 0.85 in agreement with previous empiric estimations for B₆O and experimental values for other boron-rich solids has been reported. p, V, T-рівняння стану надтвердого субоксиду бору B₆₀ було поміряно до 6 ГПа і 2700 К в багатопуансонному апараті високого тиску методом дифракції синхротронного випромінювання. Для опису експериментальних даних було запропоновано теоретичне p, V, T-рівняння стану в наближенні постійного значення параметра Андерсена-Грюнайзена δT. Модель включає модуль стиснення B₀ =181 ГПа і його першу похідну по тиску B₀′ = 6 при 300 К; два параметри, що описують термічне розширення при 0,1 МПа, а саме a = 1,4∙10–5 К–1 і b = 5∙10⁻⁹ К⁻², а також δT = 6. Хорошу відповідність між розрахованими і експериментальними ізобарами було досягнуто аж до абсолютної зміни обсягу в 5 % порівняно з початковим об’ємом V0 при 0,1 МПа і 300 К. Отримані значення термічного розширення при 0,1 МПа добре узгоджуються не тільки з експериментальними даними, але і з теплоємністю cp при атмосферному тиску, модулем стиснення B₀ і параметром δT, що описує зміну модуля стиснення з об’ємом/температурою. Отримане значення параметра Грюнайзена γ = 0,85 знаходиться у відповідності з емпіричними оцінками для B₆₀ і експериментальними значеннями для інших сполук з великим вмістом бору. p, V, T-уравнение состояния сверхтвердого субоксида бора B₆₀ было измерено до 6 ГПа и 2700 К в многопуансонном аппарате высокого давления методом дифракции синхротронного излучения. Для описания экспериментальных данных было предложено теоретическое p, V, T-уравнение состояния в приближении постоянного значения параметра Андерсена-Грюнайзена δT. Модель включает модуль сжатия B₀ = 181 ГПа и его первую производную по давлению B₀′ = 6 при 300 К; два параметра, описывающих термическое расширение при 0,1 МПа, а именно a = 1,4∙10–5 К–1 и b =5∙10⁻⁹ К⁻², а также δT = 6. Хорошее соответствие между рассчитанными и экспериментальными изобарами было достигнуто вплоть до абсолютного изменения объема в 5 % по сравнению с исходным объемом V0 при 0,1 МПа и 300 К. Полученные значения термического расширения при 0.1 МПа хорошо согласуются не только с экспериментальными данными, но и с теплоемкостью cp при атмосферном давлении, модулем сжатия B₀ и параметром δT, описывающим изменение модуля сжатия с объемом/температурой. Полученное значение параметра Грюнайзена γ = 0,85 находится в соответствии с эмпирическими оценками для B₆₀ и экспериментальными значениями для других соединений с большим содержанием бора.